Transvenous Embolization of Cavernous and Paracavernous Dural Arteriovenous Fistula through the Facial Vein: Report of 12 Cases - Myeong Jin Kim; Yong Sam Shin; Yon Kwon Ihn; Byung Moon Kim; Pyeong Ho Yoon; Se-yang Oh; Bum-soo Kim (Neurointervention, 2013)
PurposeThe aim of this study was to evaluate the feasibility and safety of the transfacial venous embolization of cavernous or paracavernous dural arteriovenous fistula (DAVF) in which approach via inferior petrosal sinus (IPS) was not feasible.Materials and MethodsWe identified the cases of transfacial venous embolization of cavernous sinus (CS) or adjacent dural sinuses from the neurointerventional database of three hospitals. The causes and clinical and angiographic outcomes of transfacial venous embolization were retrospectively evaluated.ResultsTwelve patients with CS (n = 11) or lesser wing of sphenoid sinus (LWSS, n = 1) DAVF were attempted to treat by transvenous embolization via ipsilateral (n = 10) or contralateral (n = 2) facial vein. Trans-IPS access to the target lesion was impossible due to chronic occlusion (n = 11) or acute angulation adjacent the target lesion (n = 1). In all twelve cases, it was possible to navigate through facial vein, angular vein, superior ophthalmic vein, and then CS. It was also possible to further navigation to contralateral CS through intercavernous sinus in two cases, and laterally into LWSS in one case. Post-treatment control angiography revealed complete occlusion of the DAVF in eleven cases and partial occlusion in one patient, resulting in complete resolution of presenting symptom in eight and gradually clinical improvement in four patients. There was no treatment-related complication during or after the procedure.ConclusionIn the cavernous or paracavernous DAVF in which trans-IPS approach is not feasible, the facial vein seems to be safe and effective alternative route for transvenous embolization.